Preliminary evidence for developing safe and efficient fecal microbiota transplantation as potential treatment for aged related cognitive impairments - Chen, Xiaoxia; Zhang, Wanling; Lin, Zhijun; Zheng, Chunyan; Chen, Shufang; Zhou, Haihong; Liu, Zhou (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Recent studies have reported that gut microbiota is closely associated with cognitive fuction. Fecal microbiota transplantation (FMT) may be a potential treatment for cognitive impairment, but its efficacy in patients with cognitive impairment is unknown. Objectives: This study aimed to investigate the efficacy and safety of FMT for cognitive impairment treatment. Methods: Five patients aged 54–80 years (three women) were enrolled in this single-arm clinical trial from July 2021 to May 2022. The Montreal Cognitive Assessment-B (MoCA-B), Activities of Daily Living (ADL), and the cognitive section of the Alzheimer’s Disease Assessment Scale (ADAS-Cog) were assessed at days 0, 30, 60, 90, and 180. Additionally, stool and serum samples were obtained twice before FMT was administered and six months after the treatment. The structure of fecal microbiota was analyzed by 16S RNA gene sequencing. Serum samples were analyzed for metabolomics and lipopolysaccharide (LPS)-binding proteins by liquid chromatography-mass spectrometry and enzyme-linked immunosorbent assay, respectively. Safety was assessed based on adverse events, vital signs, and laboratory parameters during FMT and the follow-up period. Results: The MoCA, ADL, and ADAS-Cog scores of patients with mild cognitive impairment (patients C and E) after FMT were improved or maintained compared with those before transplantation. However, patients with severe cognitive impairment (patients A, B, and D) had no worsening of cognitive scores. Fecal microbiota analysis showed that FMT changed the structure of gut microbiota. The results of serum metabolomics analysis suggested that there were significant changes in the serum metabolomics of patients after FMT, with 7 up-regulated and 28 down-regulated metabolites. 3b,12a-dihydroxy-5a-cholanoic acid, 25-acetylvulgaroside, deoxycholic acid, 2(R)-hydroxydocosanoic acid, and P-anisic acid increased, while bilirubin and other metabolites decreased. KEFF pathway analysis indicated that the main metabolic pathways were bile secretion and choline metabolism in cancer. No adverse effects were reported throughout the study. Conclusions: In this pilot study, FMT could maintain and improve cognitive function in mild cognitive impairment by changing gut microbiota structure and affecting serum metabolomics. Fecal bacteria capsules were safe. However, further studies are needed to evaluate the efficacy and safety of fecal microbiota transplantation. ClinicalTrials.gov Identifier: CHiCTR2100043548.